Zaključna poročila ARRS (2017)
Public funding of research work is the foundation stone of a country's research system. To this aim, countries set up public agencies that through public tenders evaluate and select the best research projects for funding. The Slovenian Research Agency performs professional, development and executive tasks related to the implementation of the adopted Research and Innovation Strategy of Slovenia within the framework of the valid budget memorandum and the state budget; in accordance with its founding, it also performs other tasks of promoting research activity. The Agency performs duties in the public interest provided by law, with the aim of ensuring permanent, professional and independent decision-making on the selection of programmes and projects that are financed from the national budget and other sources of financing. The collection comprises the Agency's reports on completed researches and targeted research projects, research programs and postdoctoral projects. In cooperation with the Agency, NUK has been collecting them in electronic form since 2007. All reports are freely accessible.
The Collection contains reports on completed research and target research projects, research programmes and postdoctoral projects that are collected by the National and University Library of Slovenia in cooperation with the Slovenian Research Agency since 2007. All reports are accessible without restrictions.